Operational and economic aspects of Spirulina-based biorefinery. (November 2019) - Costa, Jorge Alberto Vieira; Freitas, Barbara Catarina Bastos; Rosa, Gabriel Martins; Moraes, Luiza; Morais, Michele Greque; Mitchell, B. Greg
Highlights: Spirulina biorefinery contribute to greenhouse gases fixation and effluent treatment. More than 30% of the world biomass production is from genus Spirulina . Biorefineries are the best alternative for the economic performance of Spirulina . Abstract: Microalgae biorefinery systems have been extensively studied from the perspective of resources, energy expenditure, biofuel production potential, and high-added value products. The genus Spirulina ( Arthrospira ) stands out among the microalgae of commercial importance. It accounts for over 30% of biomass produced globally because of high protein concentration and, carotenoid and phycocyanin content. Spirulina cultivation can be used to reduce greenhouse gases and for effluent treatment. Furthermore, its cellular morphology facilitates biomass recovery, which contributes to the process cost reduction. Spirulina biomass is widely applicable in food, feed, cosmetics, biofertilizers, biofuels, and biomaterials. A feasibility analysis of Spirulina biorefinery would provide specific information for the decision-making for the improvement of the Spirulina production process. In that context, this review aimed to present a parameter assessment to contribute to the economic viability of Spirulina production in a biorefinery system.